New Histone Lysine Acylation Biomarkers and Their Roles in Epigenetic Regulation. Issue 4 (26th April 2023) - Fu, Qianyun; Cat, Amber; Zheng, Y. George
Abstract: Protein posttranslational modification (PTM) is a biochemical mechanism benefitting cellular adaptation to dynamic intracellular and environmental conditions. Recently, several acylation marks have been identified as new protein PTMs occurring on specific lysine residues in mammalian cells: isobutyrylation, methacrylation, benzoylation, isonicotinylation, and lactylation. These acylation marks were initially discovered to occur on nucleosomal histones, but they potentially occur as prevalent biomarkers on non‐histone proteins as well. The existence of these PTMs is a downstream consequence of metabolism and demonstrates the intimate crosstalk between active cellular metabolites and regulation of protein function. Emerging evidence indicates that these acylation marks on histones affect DNA transcription and are functionally distinct from the well‐studied lysine acetylation. Herein, we discuss enzymatic regulation and metabolic etiology of these acylations, 'reader' proteins that recognize different acylations, and their possible physiological and pathological functions. Several of these modifications correlate with other well‐studied acylations and fine‐tune the regulation of gene expression. Overall, findings of these acylation marks reveal new molecular links between metabolism and epigenetics and open up many questions for future investigation. © 2023 The Authors. Current Protocols published by Wiley Periodicals LLC.